Fertirrigation Wastewater Use for the Irrigation of Tomato and Eggplant Seedlings - Alves, Rita de Cássia [UNESP]; Oliveira, Kevein Ruas [UNESP]; Sousa Júnior, Gilmar da Silveira [UNESP]; Oliveira, Francisco de Assis; Silva, Ricardo Carlos Pereira da; Gratão, Priscila Lupino [UNESP] (Taylor & Francis, 2022)
Wastewater reuse from fertirrigation has become a new strategy for sustainable crop production, especially because there is a need to save fresh water. It can also reduce fertilizer costs and environmental pollution. This work aimed to evaluate the production of tomato and eggplant seedlings irrigated with wastewater reuse from fertirrigation. The experiment was carried out in a completely randomized design in a 2 × 4 factorial scheme with four replicates, where each replicate was represented by 25 seedlings. Treatments were represented by two crops (tomato and eggplant) and four concentrations of fertirrigation wastewater leachate (Treatment 1 (T1): 25%; Treatment 2 (T2): 50%; Treatment 3 (T3): 75% and Treatment 4 (T4): 100%). Seedlings were evaluated for the following parameters: number of leaves, seedling height, basal stem diameter, leaf area, total dry mass, and relative water content. With the exception of the basal stem diameter, eggplant seedlings were affected by leachate concentrations for all the other parameters evaluated, while tomato seedlings presented significant responses for all variables. It was observed that the use of concentrations between 50 and 75% of fertirrigation wastewater leachate can be a possible alternative to reduce the use of chemical fertilizers in the production of tomato and eggplant seedlings.
Keywords: leachate; nutrient recycling; Solanum lycopersicumL; solanum melogenal; water reuse